COMMUNICATION IN MARKETING (International conference on multidisciplinary science, 2025)
Business plan makers are faced with the task of selecting available communication channels. This article discusses the two types of communication channels: personal communication channels and non-personal communication channels, and how to properly organize marketing through these channels.